THE ROLE OF WOMEN IN THE POLITICAL AND SOCIAL LIFE IN NEW UZBEKISTAN (American Journal of Pedagogical and Educational Research, 2024)
The content of the article consists of an analysis of the processes related to the life of women in Central Asia, especially in Uzbekistan, their historical development, the expansion of their legal powers, their role in the life of society, and the impact on the processes of globalization. At this point, the rights of women in Uzbekistan and the mechanisms for their support, historical development processes, the opportunities given to them and the problems they face, as well as a number of proposals are mentioned.